The worlds of Japanese popular culture : gender, shifting boundaries and global cultures - Martinez, Dolores P (Cambridge University Press, 2013)
Sumo in the popular culture of contemporary Japan / Yamaguchi Masao -- Transformational magic / Tom Gill -- Akira, postmodernism and resistance / Isolde Standish -- Japan's empty orchestras / Bill Kelly -- Vampires, psychic girls, flying women and sailor scouts / Susan Napier -- Japanese women's magazines / Keiko Tanaka -- Nonchan's dream / Paul A.S. Harvey -- Media stories of bliss and mixed blessings / Halldór Stefánsson -- Cult of Oguricap / Nagashima Nobuhiro -- Soccer shinhatsubai / Jonathan Watts.